The Relation between Hamstring Strain Injury and Physical Characteristics of Japanese Collegiate Sepak Takraw Players - Kubo, Y.; Nakazato, K.; Koyama, K.; Tahara, Y.; Funaki, A.; Hiranuma, K. (International Journal of Sports Medicine, 2016)
The aim of this study was to investigate the injuries in Japanese collegiate sepak takraw players. We primarily focused on hamstring strain injury (HSI), and investigated the associated physical characteristics. The study included 77 Japanese collegiate sepak takraw players who were interviewed; data were collected regarding injuries sustained by them during the game within the past year. The hip range of motion (ROM) was measured. The total number of injuries was 48 in a year. The rate of HSI was the highest (31.3%) among all the injuries. All HSIs occurred in the dominant leg because of the sunback spike. Using the Mann-Whitney U test, significant differences in age and sport-related experience were observed between the injured group and uninjured group. Upon using logistic regression analysis, the presence of a HSI was found to be associated with the sport-related experience (adjusted odds ratio [OR], 0.30; 95% confidence interval [CI], 0.12–0.77) and the hip extension ROM (adjusted OR, 0.81; 95% CI, 0.66–0.99) after adjusting for sex, sport-related experience, and the hip ROM. HSI is the most common injury in Japanese collegiate sepak takraw players. Short sport-related experience and small hip extension ROM are related with the occurrence of HSI.
Keywords: sepak takraw; hamstring strain injury; joint range of motion; physical characteristics